2015
DOI: 10.1212/wnl.0000000000001315
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of severe vs mild GBA mutations on Parkinson disease

Abstract: These data demonstrate that mild and severe heterozygous GBA mutations differentially affect the risk and the AAO of PD. Our results have important implications for genetic counseling and clinical follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
342
2
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(360 citation statements)
references
References 40 publications
14
342
2
2
Order By: Relevance
“…Among these, 5 (1.8%) carried one of the two founder mutations in SMPD1 - 4 had the c.996delC (fsP330) and 1 carried the L302P mutation. One patient harbored the SMPD1 R496L mutation, which was previously shown not to increase the risk for PD [23], and therefore was excluded from the analyses. Of the 54 (20%) PD patients who harbored 1 of the 6 founder mutations in GBA , 45 carried mild mutations (N370S, n = 42 and R496H, n = 3) and 9 carried severe mutations (84GG, n = 8 and V394L, n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, 5 (1.8%) carried one of the two founder mutations in SMPD1 - 4 had the c.996delC (fsP330) and 1 carried the L302P mutation. One patient harbored the SMPD1 R496L mutation, which was previously shown not to increase the risk for PD [23], and therefore was excluded from the analyses. Of the 54 (20%) PD patients who harbored 1 of the 6 founder mutations in GBA , 45 carried mild mutations (N370S, n = 42 and R496H, n = 3) and 9 carried severe mutations (84GG, n = 8 and V394L, n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…GBA mutations can be classified as mild (N370S and R496H) and severe (84GG, IVS2 + 1, V394L, D409H, L444P, and RecTL). It has been shown that carriers of severe GBA mutations present with a 4- to 5-year earlier age of PD onset compared to mild GBA mutation carriers [23]. Recently, Ashkenazi founder mutations in the SMPD1 gene [p.L302P, c.996delC (fsP330), but not p.R496L], which cause Niemann-Pick disease type A, were reported in excess in PD patients [14,15,24].…”
Section: Introductionmentioning
confidence: 99%
“…46,65 The classification of GBA mutations as "severe" or "mild" according to the type of GD that they lead to (severe mutations lead to the neuropathic GD types and mild mutations lead to the non-neuropathic type), 66 is also valid for PD, as carriers of severe GBA mutations have higher risk and earlier onset compared to mild GBA mutation carriers. 67 It is still unclear how GBA mutations lead to PD, and several hypotheses have been raised, including mechanisms involving lossof-function or gain-of-function mutations. 68 First, it was demonstrated that chemical inhibition of GBA can lead to accumulation of SNCA, 69 a finding that was later replicated in other models with GBA mutations.…”
Section: Gba-gaucher Diseasementioning
confidence: 99%
“…This can be explained by the fact that null GBA mutations, which result in lack of expression of GBA, also cause PD. 67 Hence, if no protein is produced, it cannot cause a toxic effect, and loss of function is more likely to be the cause of increased susceptibility for PD.…”
Section: Gba-gaucher Diseasementioning
confidence: 99%
“…No difference was observed in tremor and dyskinesia between GBA and idiopathic cases in one series [49], although a large European series reported that levodopa induced dyskinesia was more severe in PD with GBA mutations than with controls [48]. Severity of the GBA mutation in terms of its effect on enzyme activity, is associated with earlier age of onset [48,50].…”
Section: Motor Featuresmentioning
confidence: 93%